Pendidikan Kewarganegaraan dalam Kehidupan Bersosialisasi dan Membangun Karakter Bangsa pada Anak Usia Dini di TK Bhakti Pertiwi Geger Balongwangi Tikung Lamongan - Sumani Sumani; Dwi Setyawati; Lailis Saadah; Priyastutik Priyastutik; Erdianto Widogo; Arfiansyah Dewa Artija; Suyono Suyono (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to provide an overview of the role of Citizenship Education in social life and building national character in early childhood. This research uses a qualitative approach. The data in the research are the results of interviews from residents of Bakti Pertiwi Kindergarten, Geger Hamlet, Balongwangi Village, Tikung Lamongan District. The results show that at Bakti Pertiwi Kindergarten, citizenship education has been implemented in daily learning, this has had an impact on socialization and character formation. early childhood at Bakti Pertiwi Kindergarten.